2004
DOI: 10.1179/136404604225022757
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and strength of a squeeze cast aluminium piston alloy composite reinforced with alumina short fibre using Al2O3binder

Abstract: Alumina short fibre preforms were fabricated using an Al 2 O 3 binder and infiltrated with aluminium piston alloy melt by squeeze casting. Al 2 O 3 binder is thermodynamically more stable than the conventional SiO 2 binder and reduces the fibre/matrix interfacial reaction. The effects of fibre volume fraction, temperature and heat treatment on the yield strength and tensile strength of the composite were investigated. The Al 2 O 3 binder provided a satisfactory interfacial bond between the fibre and the matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The alumina ber volume fraction of the AFR is smaller than the carbon ber-reinforced composite and it might not be suitable for the comparative specimen. The author 11) conrmed that the short alumina ber-reinforced composite exhibited the high temperature strength at the ver volume of 15% and the composite with higher volume fraction exhibited lower strength. Therefore, this composite was selected as the comparative specimen which has the high temperature strength.…”
Section: Methodsmentioning
confidence: 94%
“…The alumina ber volume fraction of the AFR is smaller than the carbon ber-reinforced composite and it might not be suitable for the comparative specimen. The author 11) conrmed that the short alumina ber-reinforced composite exhibited the high temperature strength at the ver volume of 15% and the composite with higher volume fraction exhibited lower strength. Therefore, this composite was selected as the comparative specimen which has the high temperature strength.…”
Section: Methodsmentioning
confidence: 94%
“…The fiber volume fraction in the preform was controlled at 15 vol%. It is reported that 15 vol% is the most suitable for improving the high temperature strength of the AC8A alloy [5]. Figure 2 shows the appearance ( Fig.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 95%
“…Another advantage of the alumina fiber is that a chemical reaction with the aluminum melt is difficult to occur, and that makes the fabrication of the composite by a low-cost casting process easier. The alumina fiber-reinforced aluminum alloy composites have not only been fundamentally studied [5][6][7], but also made in trials or put into practical use [8]. From the viewpoint of the practical use of such composites, it is very important to clarify their machinability.…”
Section: Introductionmentioning
confidence: 99%
“…High abrasion resistance [3], good strength at high temperatures, low density, and high oxidation resistance of Al 2 O 3 as a reinforcement have developed a special class of advanced materials, i.e. Al-Al 2 O 3 composites [4][5][6].…”
Section: Introductionmentioning
confidence: 99%